'How do girls manage?', 1940 (1940)
1940 1939-1945 "'How do girls manage?', 1940" [HFR0163], 1940 Article in 'The Post' newspaper from the Union of Post Office Workers, 14 December, 1940, which details the cost of living for single young working women living in rented accommodation.